Effect of Multimedia Instructional Strategy on Students’ Academic Achievement in Mechanical Trades in Technical Colleges (Journal of Education and Development, 2020)
The need to improve academic performance of technical college students in mechanical trades necessitated this study. Thus the study proceeded to determine the effect of teaching mechanical trades concepts with multimedia on students’ academic achievement in technical colleges. One research question guided the study and one null hypothesis was tested at 0.05 alpha level. The study employed a pretest, posttest, quasi-experimental design involving two non-equivalent intact groups, (experimental group and the control group). The population was 123 National Technical College II (NTC II) students offering mechanical trades in Ondo State Nigeria. A sample of 84 students participated in the study. Purposive sampling technique was used to select two intact classes in Government technical colleges from two different local government areas of the State. Three data collection instruments, namely, the lesson plan for the experimental group, the lesson plan for the control group and the Mechanical Trade Achievement Test (MTAT) were used for the study. These were validated by three experts (one from Measurement and Evaluation unit and two from Technology and Vocational Education) all from Nnamdi Azikiwe University, Awka. The MTAT was subjected to a reliability test using Kuder Richardson 21 (KR-21) formula to yield the reliability coefficient of 0.82. Mean as well as Analysis of Covariance (ANCOVA) were used to analyze at 0.05 level of significance the data collected for the study. Findings of the study revealed that teaching with multimedia was more effective in enhancing student’s achievement in mechanical trade. Based on the findings, it was concluded that multimedia technology is more effective in improving student’s achievement in mechanical trade. Consequently it was recommended that technical college mechanical trade teachers should adopt teaching with multimedia.